Penyuluhan Tentang Hipertensi, Mengukur Tekanan Darah Pada Lansia Binaan STIKes Bala Keselamatan Palu - Yulian Heiwer Matongka; Fitri Arni Rasyidi; Saiful Ambodale (CV. Multi Kreasi Media, 2025)
Elderly people are part of human development, a final stage. According to Law No. 13 of 1998 concerning Health, elderly people are defined as those who have reached the age of 60. At this age, physical and functional declines often occur, requiring assistance or explanations regarding the aging process. The number of elderly people in South Birobuli Village is 41 (13.2%). Five (33.3%) have hypertension and one (1.6%) has had a stroke. A survey of several elderly people revealed they have many questions about the causes of hypertension and how to manage it. The measures taken included education about hypertension, blood pressure checks, and exercise. Results: Of the 15 individuals with high blood pressure, 5 (33.3%) had high blood pressure. Counseling was provided to those with high blood pressure and recommendations for further examination at the Community Health Center (Puskesmas), and 10 participated in exercise.